The impact of a proposed educational site in providing students of the Department of Curriculum and Instruction at Umm Al Qura University the skills of designing electronic courses - Masoudi, ‏​‏​‏​​‏​‏​​‏​‏​‏​‏​‏​‏ Hana Bint Saad bin Barki (Journal of Educational and Psychological Sciences, 2018)
The aim of the study was to find out the impact of an educational site in providing the students of the Department of Curriculum and Teaching Methods at Umm Al Qura University with the skills of designing electronic courses. To achieve the objectives of the study, the researcher used the semi-experimental method. The list of skills of designing e-courses and building the cognitive achievement test, (25) female students of the Department of Curriculum and Teaching Methods at Umm Al-Qura University. They were trained according to the method of integrated learning. In order to obtain the results of the study, the researcher used the program group Statistical Packages for Social Sciences (SPSS). The study results in the following results: - There is a statistically significant difference at the mean level (0,05αα) between the average scores of the students in the experimental group in the cognitive achievement test for the skills of designing e-courses via the educational site; in the tribal applications, they obtained an average of 17,20, (26.16) for the benefit of the post application. - There is a statistically significant difference between the mean scores of the experimental group in the assessment card of the e-courses through the educational site in the two tribal applications. The average score was (30.96) and the average (57, 72), in favor of the post-application. In light of the results of the study, the researcher recommended a number of recommendations. The most important of these recommendations were: To benefit from the proposed educational site in the teaching of educational courses for various disciplines in the undergraduate stages and to hold training courses for faculty members;